Nuclear medicine in district general hospitals. Issue 6201 (24th November 1979) - Croft, D
Abstract : Nuclear medicine is a recognised clinical specialty both nationally and internationally. Compared with other countries, it is inadequately developed in Britain, particularly in district general hospitals. To create clinical radioisotope services at district level physicians or radiologists with experience in nuclear medicine need to be trained and appointed. Such appointments would allow facilities to evolve that would provide either a comprehensive nuclear medicine service formed around a physician or an imaging service based on a radiologist. Such units would improve the care of patients at a reasonable recurring cost of 15 pounds–30 pounds per investigation.